Comparison of Hospitals Supporting Quality Assurance - Selbmann, H. K.; Warncke, W.; Eissner, H.J. (Methods of Information in Medicine, 1982)
In 1980, 159 obstetric departments took part in the Bavarian Perinatal Survey. For each newborn a questionnaire comprising about 100 items was filled in. The main objective of the Bavarian Perinatal Survey is the quality assurance of obstetric care. This objective is to be supported by appropriate hospital comparisons permitting each hospital a determination of its position relative to the other hospitals. For special subgroups of patients, hospital profiles were developed. The indirect standardization of rates and the logistic regression were used for a global comparison of hospitals. A procedure was defined to detect remarkable deviations between hospitals. These deviations should be considered as signals for clarifying discussions between the participating obstetricians.
Keywords: Quality Assurance; Survey; Perinatology; Hospital Profiles; Casemix Adjustment